Ag nanoparticles immobilized on new magnetic alginate halloysite as a recoverable catalyst for reduction of nitroaromatics in aqueous media - Mohammadi, Pourya; Heravi, Majid; Daraie, Mansoureh (Scientific reports, 2021)
Amines can be applied in the synthesis of various important compounds such as dyes, drugs, polymers, pharmaceutical products, and biologically active materials. The significant subject in the preparation of amines is the selection of the most effective heterogeneous catalyst to get the best catalytic efficiency, stability, recoverability, and reusability. For this target, we prepared new alginate magnetically recoverable nanocatalyst by stabilization of Ag nanoparticles on the surface of the halloysite (HS) [HS-Alginate-Ag/Fe 3 O 4 ]. Several detection methods confirmed the production of HS-Alginate-Ag/Fe 3 O 4 nanocatalyst and the results obtained were well explained in the context. HS-Alginate-Ag/Fe 3 O 4 presented good catalytic performance for the hydrogenation of nitro compounds using NaBH 4 as the reducing agent and hydrogen donor. The good activity and durability of this catalyst can be attributed to the good dispersion and nano-sized particle of silver nanoparticles.